Research into factors of motivation and self-regulation in sporting activities - Gvozdetskaya, S.S.; Sheshukova, O.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the relationship between motivation and self-management in athletes. Methods and structure of the study. The research was conducted using two methodologies: ‘Assessment of motives in professional sports’ by L. Pelletier and R. Vallandry (adapted by K.A. Bocharov et al.) and ‘Methodology for studying self-management’ by Yu. Kuly and A. Furman (adapted by O.V. Mitina and E.I. Rasskazova). The sample consisted of 50 active athletes (28 young women and 22 young men) aged 16 to 21, engaged in various sports (football, volleyball, figure skating, etc.). Statistical analysis of the data was performed using the jamovi Desktop programme, including correlation analysis based on Spearman's rank correlation criterion. Results and conclusions. The analysis showed that internal motivation prevails among athletes, which is confirmed by high scores on the ‘Emotions’ and ‘Self-development’ scales. External stimuli, such as social approval or a sense of duty, play a less significant role. Respondents demonstrate a strong internal motivational base, contributing to sustained engagement in the training process. Athletes showed higher levels of cognitive self-regulation, internal motivation, and planning than on the emotional regulation and volitional activity scales. This may limit their ability to cope with stress, overcome setbacks, and achieve long-term goals. Correlation analysis revealed significant positive links between the internal motivation scales and self-management components, which is consistent with self-determination theory. The inverse links between demotivation and initiative and overcoming setbacks indicate a decline in the regulatory system when the personal meaning of the activity decreases.